The Effectiveness of Pure Honey Administration on Hemoglobin Levels in Pregnant Women at TPMB Choirul Mala, Palembang City - Deby Meitia Sandy; Suci Sulistyorini (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Anemia during pregnancy remains a significant global health issue, particularly in low- and middle-income countries. Iron (Fe) tablets are the standard treatment, but alternative natural supplements such as pure honey may enhance hemoglobin levels through their nutritional and antioxidant properties. This study aims to  analyze the effectiveness of pure honey combined with Fe tablets on hemoglobin levels among pregnant women with anemia at TPMB Choirul Mala, Palembang. This quasi-experimental study employed a pretest-posttest control group design. A total of 30 pregnant women with anemia were selected through purposive sampling from a population of 66 who attended ANC visits between September and December 2024. Participants were divided equally into intervention and control groups. The intervention group received 2 tablespoons of certified pure honey and one 60 mg Fe tablet daily for 4 weeks, while the control group received only the Fe tablet. Hemoglobin levels were measured before and after the intervention. Data were analyzed using the Wilcoxon and Mann–Whitney tests. The intervention group showed a significant increase in mean hemoglobin level from 9.2 g/dL to 10.8 g/dL (p = 0.002), while the control group increased from 9.0 g/dL to 10.4 g/dL (p = 0.004). The difference in hemoglobin increase between groups was statistically significant (p = 0.041). The combination of pure honey and Fe tablets is more effective in increasing hemoglobin levels than Fe tablets alone. Pure honey may serve as a beneficial complementary therapy in managing anemia during pregnancy.